ANTI-DIABETIC ACTIVITY OF HYDROALCOHOLIC EXTRACT OF EUGENIA JAMBOLANA LEAVES IN ALLOXAN INDUCED DIABETIC RATS - SHANKAR, M.; Suthakaran, R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2014)
Objective: The present study was carried out to evaluate the antidiabetic activity of hydroalcoholic extracts of Eugenia jambolana leaves. Methods: The hydroalcoholic extracts of Eugenia jambolana by alloxan induced diabetic rats for 20 days. At high dose (400 mg/kg) it is exhibited significant anti- hyperglycaemic activity than hydroalcoholic extracts of Eugenia jambolana at low dose (200 mg/kg) in diabetic rats. Results: The hydroalcoholic extracts of Eugenia jambolana also showed improvement in parameters like body weight, Serum Cholesterol level and hepatic glycogen as well as regeneration of beta-cells of pancreas in diabetic rats. Conclusion: Histopathological studies reinforce the healing of kidney by hydroalcoholic extracts of Eugenia jambolana leaves as a possible mechanism of their antidiabetic activity. The present study provides a proof for the strong chemo taxonomical relationship for the plant